DOES CLIENT IMPORTANCE AFFECT AUDIT QUALITY IN MODERATION? - Jessica; Ria Ginting, Rasinta; Noviyanti Simorangkir, Enda (Економіка та суспільство, 2023)
The financial report is a report that is very necessary in making decisions. For this reason, a quality audit is needed that can truly explain the condition of the company. Good audit quality can provide the right information for its users, while poor audit quality can cause many losses, both internal and external. The purpose of this research is to examine the influence of audit tenure, audit committee, and public accounting firm industry specialization on audit quality with client importance as a moderator. The data in this research uses secondary data obtained from the 2019 to 2021 financial reports listed on the Indonesia Stock Exchange using the purposive sampling method and using the SPSS program in data processing. The independent variables in this research are audit tenure, audit committee, and public accounting firm industry specialization. Audit tenure is calculated based on the number of years of engagement, the first year is given the number 1 and 1 is added for the following years. The audit committee is calculated based on the number of audit committee members. Public accounting firm industry specialization is calculated based on the number of companies audited by the same auditor divided by the number of companies, and if the result is more than 20% it is given the number 1, otherwise it is given the number 0. The dependent variable in this research is audit quality which is given the number 1 for the Big Four and 0 for the Non-Big Four, and the moderating variable is client importance which is calculated by the natural logarithm of total assets divided by the natural logarithm of total assets audited by the same auditor. This research uses logistic regression analysis in data processing because the independent variable indicators are dichotomous. The results of this research are that audit tenure affects audit quality, audit committees have an effect on audit quality, and public accounting firm industry specialization has no effect on audit quality. Client importance as moderation also cannot influence audit tenure, audit committee, and public accounting firm industry specialization on audit quality.